2016
DOI: 10.11124/jbisrir-2016-003188
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and experience of arts-based pedagogy among undergraduate nursing students: a mixed methods systematic review

Abstract: Nurse educators should consider using ABP as students found that this approach offered a meaningful way of learning and resulted in the development of important competencies for professional nursing. The QN studies provide a very low level of evidence that ABP improved students' knowledge acquisition, level of empathy, attitude toward others, emotional states, level of reflective practice, learning behaviors and aspects of cognitive/ethical maturity. Although the QN findings can inform future research, the evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 95 publications
2
36
0
2
Order By: Relevance
“…In learning through art, the learner approaches a subject matter by creating art, responding to art, or performing artistic works not by studying art as a theoretical discipline (Rieger and Chernomas, 2013). This art-based learning (ABL) has been used successfully in healthcare education (Wikström, 2003; Rieger et al., 2016). For instance, using a work of art as a teaching method is effective in increasing students’ observational skills, empathy (i.e., abilities in empathizing with the patient and develop compassion), nonverbal communication, and interpersonal relationships, in comparison with traditional teaching programs (Wikström, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In learning through art, the learner approaches a subject matter by creating art, responding to art, or performing artistic works not by studying art as a theoretical discipline (Rieger and Chernomas, 2013). This art-based learning (ABL) has been used successfully in healthcare education (Wikström, 2003; Rieger et al., 2016). For instance, using a work of art as a teaching method is effective in increasing students’ observational skills, empathy (i.e., abilities in empathizing with the patient and develop compassion), nonverbal communication, and interpersonal relationships, in comparison with traditional teaching programs (Wikström, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In this narrative, medication packages were used to create an image of a human brain as a way of demonstrating the reconciliation between therapeutic relationships and practical nursing care as one interchangeable concept. A literature review suggested that arts-based learning methods can have an effect on promoting reflecting, creating meaning, developing professional nursing competencies, and improving empathy and knowledge acquisition among undergraduate nursing students (Rieger, Chernomas, McMillan, Morin, & Demczuk, 2016). Specific art modalities include murals, poetry, sculpture, dance, dramatic arts, masks, music, stories, and film (Rieger et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A literature review suggested that arts-based learning methods can have an effect on promoting reflecting, creating meaning, developing professional nursing competencies, and improving empathy and knowledge acquisition among undergraduate nursing students (Rieger, Chernomas, McMillan, Morin, & Demczuk, 2016). Specific art modalities include murals, poetry, sculpture, dance, dramatic arts, masks, music, stories, and film (Rieger et al., 2016). Another form of creative reflection is the use of poetry, which has been found to enhance empathy skills in nursing students caring for geriatric clients (Adams & Scott, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through the search for the improvement of nurses, educators are encouraged to adopt different pedagogical approaches, and the growing interest in evidence-based education is a current reality based on the need for reflection and student involvement. 1 To envisage scenarios in which learning can be transformed into meaningful experience has become the target of many teachers who aim at the revitalization of the teaching-learning process. 2 By means of the implementation of innovative educational strategies, isolated or combined, active and dynamic learning proposals 3 are required to provide new and robust information, especially facilitated by the individual's own knowledge structure known as meaningful learning.…”
mentioning
confidence: 99%